Comparison of efficiency measures for Spanish first division football teams using data envelopment and stochastic frontier analyses - Manuel Espitia-Escuer; Lucía Isabel García-Cebrián (Atlantic Review of Economics, 2014)
The aim of this study was to analyse the robustness of the efficiency ratios calculated by the original version of Data Envelopment Analysis (DEA), the modified version, as proposed by Andersen and Petersen (1993), and stochastic frontier analysis. The study was performed on the football teams that played in the Spanish football First Division between 1998 and 2010. The results show that consistency conditions are generally met between the two versions of the DEA, but the correlation between them and stochastic frontier analysis is less. The conclusions offer some possible interpretations of the discrepancies identified.
Keywords: 330